Colorimetric sensing of anions in aqueous solution using a charge neutral, cleft-like, amidothiourea receptor: Tilting the balance between hydrogen bonding and deprotonation in anion recognition - GUNNLAUGSSON, THORFINNUR; DUKE, REBECCA MONICA; O'BRIEN, JOHN; MCCABE, THOMAS (My University, 2008)
The design, synthesis and physical evaluation of 1, a visible colorimetric `naked eye? pyridyl based bis-amidothiourea sensor for anions, is described. This charge neutral sensor gives rise to significant changes in the absorption spectra upon interactions with several important biological anions such as AMP and ADP in 4 : 1 DMSO?H2O solution, while ATP was not detected. These colorimetric changes are due to the formation, or the combination of hydrogen bonding complexes and/or deprotonation between these anions and 1.
PUBLISHED
Keywords: Organic chemistry; Anions